Modelling of energy metabolism and analysis of pH variations in postmortem muscle. (December 2021) - Wang, Chengcheng; Matarneh, Sulaiman K.; Gerrard, David; Tan, Jinglu
Abstract: A kinetic model structure was developed to describe the major variations in energy metabolism and to gain further understanding of pH changes in postmortem muscle experimentally observed with an in vitro glycolytic system. Comparison with experiments showed that the model could describe the kinetics of major metabolites and pH under varied conditions. Optimized model parameters definitively and consistently showed the observed effects of mitochondria, indicating a desirable level of model complexity. Simulation and analysis of pH variations based on the model suggested that phosphofructokinase activity has the strongest impact on the rate and extent of postmortem pH decline. Postmortem pH is also influenced by rates of ATP hydrolysis and glycolysis, and to a much lesser extent, pH buffering capacity. Other reactions, including those mediated by creatine kinase, adenylate kinase, and AMP deaminase, have minimal effects on postmortem pH decline.